Analysis of Game Company Restructuring: Effectiveness Assessment and Comparative Analysis of Success/Failure - Huang, Xuan (Transactions on Economics, Business and Management Research, 2024)
As a matter of fact, game industry has become booming in recent years under the occasion of the rapid development of computation techniques. As a giant company, Microsoft has its ambitious merge and acquisition planning regarding to this industry. With this in mind, this study examines the case studies of Microsoft's acquisition of Activision Blizzard in 2022 and Nintendo's internal restructuring in 2018 to demonstrate the strategy as well as performances for Microsoft in game industry. By contrastive analysis of the background, strategies, as well as outcomes of these reorganizations, this research aims to assess their effectiveness and identify success and failure factors for this M&A process. According to the analysis, the study results show that although both companies have achieved specific results after restructuring, they still face many challenges. These results also provide suggestions for corporate restructuring and the development of the game industry, as well as directions for future research.